Distributed language - Cowley, Stephen J. (Stephen John), 1955- (Benjamins current topics ;, 2011)
The volume presents language as fully integrated with human existence. On this view, language is not essentially 'symbolic', not represented inside minds or brains, and most certainly not determined by micro-social rules and norms. Rather, language is part of our ecology. It emerges when bodies co-ordinate vocal and visible gesture to integrate events with different histories. Enacting feeling, expression and wordings, language permeates the collective, individual and affective life of living beings. It is a profoundly distributed, multi-centric activity that binds people together as they go ...